CULTURAL CONTENT ANALYSIS OF AN ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL GRADE THREE IN CIANJUR, WEST JAVA - Faris, Ihsan Nur Iman (2014)
This research investigates the cultural content in an English textbook for senior high school grade three in Cianjur, West Java. The data of the research were collected from reading passages in the English textbook for senior high school entitled "Look Ahead", book three published by Airlangga publisher. To reveal what cultures are represented in the textbook, the cultural contents are categorized into the source culture, the target culture, or the international culture (Cortazzi & Jin, 1999). To reveal how the cultures are represented in the textbook, the cultural contents are categorized into the aesthetic sense, the sociological sense, the semantic sense, or the pragmatic sense (Adaskou, Britten & Fahsi, 1990). The research finds that the target culture is predominant in the textbook. The investigation found that 77.05% cultural contents refer to the target culture, 13.11% cultural contents refer to the source culture, and 09.84% cultural contents refer to the international culture. Regarding how cultures are represented in the textbook, generally culture is represented by the aesthetic sense (37.70%), the sociological sense (31.15%), the pragmatic sense (19.67%) and the semantic sense (11.48%). Based on the findings it is recommended that more source culture and international culture be included in the textbook. Keywords: Culture, the target culture, the source culture, the international culture, four senses of culture, textbooks. Penelitian ini menginvestigasi muatan budaya dalam sebuah buku pelajaran bahasa Inggris untuk kelas tiga di salah satu SMA di Cianjur. Data dalam penelitian diambil dari teks bacaan dalam buku pelajaran bahasa Inggris yang berjudul "Look Ahead" buku ketiga, diterbitkan oleh penerbit Airlangga. Untuk menyingkap budaya apa yang direpresentasikan oleh buku pelajaran, muatan budaya dikaterogikan ke dalam budaya pribumi, budaya target, dan budaya internasional (Cortazzi & Jin, 1999). Untuk menyingkap bagaimana budaya direpresentasikan di buku pelajaran, muatan budaya dikategorikan ke dalam makna estetika, makna sosiologikal, makna semantik, dan makna pragmatic (Adaskou, Britten & Fahsi, 1990). Penelitian ini menemukan bahwa budaya target diutamakan dalam buku pelajaran. Hasil investigasi menunjukan 77.05% muatan budaya merujuk pada budaya target, 13.11% muatan budaya merujuk pada budaya pribumi, dan 09.84% merujuk pada budaya internasional. Berkenaan dengan bagaimana budaya direpresentasikan, secara umum budaya direpresentasikan dengan makna estetika (37.70%), makna sosiologikal (31.15%), makna pragmatic (19.67%) dan makna semantic (11.48%). Berdasarkan temuan penelitian, direkomendasikan budaya pribumi dan budaya internasional agar mendapat proporsi lebih di dalam buku pelajaran. Kata Kunci: Budaya, budaya target, budaya pribumi, budaya internasional, empat makna budaya, buku pelajaran.